Adverse Drug Reactions and Toxicity of the Food and Drug Administration–Approved Antisense Oligonucleotide Drugs - Alhamadani, Feryal; Zhang, Kristy; Parikh, Rajvi; Wu, Hangyu; Rasmussen, Theodore P.; Bahal, Raman; Zhong, Xiao-bo; Manautou, José E. (Drug metabolism and disposition, 2022)
The market for large molecule biologic drugs has grown rapidly, including antisense oligonucleotide (ASO) drugs. ASO drugs work as single-stranded synthetic oligonucleotides that reduce production or alter functions of disease-causing proteins through various mechanisms, such as mRNA degradation, exon skipping, and ASO-protein interactions. Since the first ASO drug, fomivirsen, was approved in 1998, the U.S. Food and Drug Administration (FDA) has approved 10 ASO drugs to date. Although ASO drugs are efficacious in treating some diseases that are untargetable by small-molecule chemical drugs, concerns on adverse drug reactions (ADRs) and toxicity cannot be ignored. Illustrative of this, mipomersen was recently taken off the market due to its hepatotoxicity risk. This paper reviews ADRs and toxicity from FDA drug labeling, preclinical studies, clinical trials, and postmarketing real-world studies on the 10 FDA-approved ASO drugs, including fomivirsen and pegaptanib, mipomersen, nusinersen, inotersen, defibrotide, eteplirsen, golodirsen, viltolarsen, and casimersen. Unique and common ADRs and toxicity for each ASO drug are summarized here. The risk of developing hepatotoxicity, kidney toxicity, and hypersensitivity reactions co-exists for multiple ASO drugs. Special precautions need to be in place when certain ASO drugs are administrated. Further discussion is extended on studying the mechanisms of ADRs and toxicity of these drugs, evaluating the existing physiologic and pathologic states of patients, optimizing the dose and route of administration, and formulating personalized treatment plans to improve the clinical utility of FDA-approved ASO drugs and discovery and development of new ASO drugs with reduced ADRs. The current review provides a comprehensive analysis of unique and common ADRs and the toxicity of FDA-approved ASO drugs. The information can help better manage the risk of severe hepatotoxicity, kidney toxicity, and hypersensitivity reactions in the usage of currently approved ASO drugs and the discovery and development of new and safer ASO drugs.